Optimization of FAME production from blends of waste cooking oil and refined palm oil using biomass fly ash as a catalyst (2020)
One of the problems associated with biomass combustion is the amount of fly ashes generated and its subsequent management. The search for ways of valorizing these ashes has been a challenge for the academic and industrial community. On the other hand, used cooking oils are wastes which management is quite difficult, by they have a very important energetic potential. The goal of this work was to optimize the Fatty Acid Methyl Esters (FAME) process, recovering two residual materials (waste cooking oils (WCO), and biomass fly flash (BFA)). The optimization of the process was achieved using the response surface methodology and a Box-Benhken experimental design applied to mixtures of WCO and refined palm oil (RPO), using BFA as catalyst. The influence on FAME yield of four variables (catalyst loading, methanol/oil molar ratio, RPO/WCO ratio and reaction temperature) was studied. The higher FAME yield achieved was 73.8% for the following operating conditions: 13.57 wt% of catalyst loading, 6.7 of meth-anol/oil molar ratio, 28.04 wt% of RPO in the oil mixture with WCO and 55 C for the reaction temperature. The reusability of the BFA catalyst in the process was also studied through three successive usage cycles finding no loss of catalytic activity.